On the Mechanism by which Bovine Fibrinogen Induces the Release and Availability Reaction of Human Blood Platelets - Kubisz, P; Suranová, J (Thrombosis and Haemostasis, 1973)
Bovine fibrinogen can aggregate human blood platelets by a direct mechanism (first wave) and also indirectly by releasing endogenous ADP (second wave).A primarily non-altered surface structure of the thrombocytes is important for the induction of the first wave.Under certain conditions a second aggregation wave, concomitant with the release and the availability reaction is elicited.Besides the cells’ contact, the presence of ADP and calcium ions are necessary for the induction of the release reaction in human platelet rich plasma.The changes induced by bovine fibrinogen thus follow the same pattern as the irreversible phase of aggregation, linked to release as induced by ADP.